Actions of reserpine on the digestive system - Ulbilluz, Rodrigo (1956)
Pharmacological and therapeutic properties of Rauwolfia serpentina, whose roots are used for centuries in India, have attracted considerable interest of western medicine in recent years. In the laboratory, Rauwolfia and its alkaloids, especially reserpine, produce sedation and reduction of spontaneous activity in all species studied namely guinea pigs. dogs, rabbits, cats, mice, rats and monkeys.